Short-term outcomes of inborn v. outborn very-low-birth-weight neonates (<1 500 g) in the neonatal nursery at Groote Schuur Hospital, Cape Town, South Africa - L Gibbs (South African Medical Journal, 2017)
Background. The Groote Schuur Hospital (GSH) neonatal nursery provides level 3 care for the Metro West Health District in the Western Cape Province of South Africa. Worldwide, very-low-birth-weight (VLBW) neonates delivered in level 3 neonatal units have better outcomes than those transported from other facilities. Objectives. To identify the characteristics and outcomes of VLBW neonates at GSH, with emphasis on differences between inborns and outborns. Methods. This was a retrospective cohort study. VLBW neonates admitted to the GSH neonatal nursery between 1 January 2012 and 31 December 2013 were enrolled on the Vermont Oxford Network database and reviewed. Results. Of 1 032 VLBW neonates enrolled, 906 (87.8%) were delivered at GSH and 126 (12.2%) were outborn. Access to antenatal care, antenatal steroids and inborn status were statistically significant predictors of mortality and survival without morbidity. The mothers of inborn patients were more likely than those of outborn patients to have received antenatal care (89.1% v. 57.9%; p<0.0001) and antenatal steroids (64.2% v. 15.2%; p<0.0001). Inborns required less ventilatory support (16.2% v. 57.9%; p<0.0001) and surfactant administration than outborns (25.3% v. 65.1%; p<0.0001), and developed less late infection (8.8% v. 23.4%; p<0.0001), severe intraventricular haemorrhage (3.7% v. 13.9%; p<0.0001) and chronic lung disease (5.3% v. 13.4%; p=0.003). The incidence of necrotising enterocolitis was similar in the two groups (5.9% v. 8.7%; p=0.227). The mortality rate was 18.4% for inborns and 33.3% for outborns (p<0.0001). Mortality declined as birth weight increased. Of the survivors, 85.0% of inborns and 70.2% of outborns did not develop serious morbidity (p=0.003). Conclusions. VLBW neonates delivered at GSH had better outcomes than their outborn counterparts. Perinatal regionalisation is beneficial to our patients, with antenatal care, timeous transfer in utero and antenatal steroids contributing to excellent outcomes.